Pelatihan Desain untuk Media Promosi Online dan Meningkatkan Daya Jual Produk di SMA Muhammadiyah 1 Surakarta - Rahmad Ardhani; Muhammad Misbahul Munir; Nutfah Ailul Ulun (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Technological developments, especially in the field of graphic design, have had a significant impact on the world of marketing. Graphic design can be a more interesting and unique communication medium because it has images and text with colors that are very beautiful to look at. More and more business people are using graphic design as their marketing medium, such as posters, banners, logos, etc. (1) Lack of knowledge regarding the use of graphic design applications means students have limited abilities, so it will be difficult to compete with others in the world of work later. Students of Sma Muhammadiyah 01 Surakarta are not yet familiar with and use the Canva application, but this is not evenly distributed across all Sma Muhammadiyah 01 Surakarta. Lack of knowledge regarding the use of graphic design applications means students have limited abilities, so it will be difficult to compete with others in the world of work later and there is a lack of marketing knowledge in the field of digital marketing. Providing material or socializing about the other side of the Canva application is expected to stimulate and motivate students at Sma Muhammadiyah 01 Surakarta to further explore material regarding Graphic Design quickly, reliably and easily. (5) and it is hoped that it can increase the skills of high school students and students. Muhammadiyah 01